Upper Airway Cell Transcriptomics Identify a Major New Immunological Phenotype with Strong Clinical Correlates in Young Children with Acute Wheezing. - Khoo, S.; Read, J.; Franks, K.; Zhang, Guicheng; Bizzintino, J.; Coleman, L.; McCrae, C.; Öberg, L.; Troy, N.; Prastanti, F.; Everard, J.; Oo, S.; et al. (2019)
Asthma exacerbations are triggered by rhinovirus infections. We employed a systems biology approach to delineate upper-airway gene network patterns underlying asthma exacerbation phenotypes in children. Cluster analysis unveiled distinct IRF7hi versus IRF7lo molecular phenotypes, the former exhibiting robust upregulation of Th1/type I IFN responses and the latter an alternative signature marked by upregulation of cytokine and growth factor signaling and downregulation of IFN-?. The two phenotypes also produced distinct clinical phenotypes. For IRF7lo children, symptom duration prior to hospital presentation was more than twice as long from initial symptoms (p = 0.011) and nearly three times as long for cough (p < 0.001), the odds ratio of admission to hospital was increased more than 4-fold (p = 0.018), and time to recurrence was shorter (p = 0.015). In summary, our findings demonstrate that asthma exacerbations in children can be divided into IRF7hi versus IRF7lo phenotypes with associated differences in clinical phenotypes.